Development of a DG management system of smart grids - Lau, Chang Yu. (2013)
This paper discusses the development of a Smart Grid management system. The created Smart Grid system will incorporate 2 feasible renewable energy sources, namely solar and wind energy. The 2 sources are regarded as Distributed Generation within the Smart Grid system. The management system aims to develop a pricing system for the Smart Grid owner to set to charge electricity consumers. Time of Use (ToU) pricing system will be introduced and Simple Levelized Cost Of Energy (SLCOE) will be used to calculate price to charge for solar and wind energy.